GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA ANGGOTA POLRI DAN ASN DI DITRESKRIMUM POLDA SUMSEL - Effendi, Elliya; Marnisah, Luis (Jurnal Ecoment Global, 2019)
This study aims to determine: (1) Effect of leadership style on the performance of National Police and ASN Members Ditreskrimum of North Sumatra Regional Police. (2) The Effect of Work Discipline on the Performance of Members of the Police and ASN Ditreskrimum of the South Sumatra Regional Police. (3) Effect of leadership style and work discipline on the performance of National Police and ASN Members Ditreskrimum of North Sumatra Regional Police. This study is categorized as a quantitative associative causal study with an instrument in the form of a questionnaire. The population in this study were 132 members of the National Police and South Sumatra Regional Police ASN. Sampling technique using Sampling Proposal. The sample in this study was to take a population or as many as 132 samples. Data collection using questionnaires and interviews. Test the validity of the instrument using Confirmatory Factor Analysis, while the reliability test uses Cronbach Alpha. The measuring instrument proved to be valid and reliable for research instruments. Multiple regression analysis is used to test the hypothesis of this study. The results of the study found that: (1) Leadership Style had a positive and significant effect on the performance of Polri and ASN Members Ditreskrimum of North Sumatra Regional Police using the t test that t counted 6.499> with t table 1.993 with a significance of 0.00 <0.05, Contributing leadership style to the performance of National Police and ASN Members Ditreskrimum of North Sumatra Regional Police is 50%. (2) Work discipline has a significant positive effect on the performance of National Police and ASN Members Ditreskrimum South Sumatra Police using t test that t count 4.021> with t table 1.993 with a significance of 0.025 <0.05, Contribution of work discipline to the performance of National Police and ASN Members Ditreskrimum Polda Sumsel by 25%. (3) Leadership style and work discipline have a positive and significant effect on the performance of National Police and ASN Members Ditreskrimum South Sumatra Police using the F test that F count 9.980> with F table 1993 with significance 0.04 <0.05, Contributions of leadership style and work discipline to explain performance Members of the Indonesian National Police and ASN Ditreskrimum Sumsel Polda amounted to 40%.Â Keywords: Leadership Style, Work Discipline, Employee Performance